2020
DOI: 10.9734/ejmp/2020/v31i1830341
|View full text |Cite
|
Sign up to set email alerts
|

Crude and Partition Extracts of Newbouldia laevis Leaves Attenuate Excitotoxin-induced Stereotypy in Mice

Abstract: Aims: This study was designed to investigate the effects of crude ethanol and partition extracts of Newbouldia laevis leaves on excitotoxin-induced stereotypy in mice. Place and Duration of Study: The study was carried out in the Laboratory of the Department of Pharmacology and Therapeutics, College of Health Sciences, Ladoke Akintola University of Technology, Ogbomoso, Nigeria, between July and October, 2020. Methodology: Following pretreatment of mice with graded doses (150 - 600 mg/kg b.w) of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
2
0
0
Order By: Relevance
“…The oral median lethal doses (LD50) of N. laevis stem-bark extract were estimated to be greater than 5000 mg/kg suggesting that the extract was relatively safe and non-toxic. 19 This result is consistent with the report of [27][28] who reported that no mortality was recorded up to 5000 mg/kg in the root and ethanol leaf extracts of N. laevis and the estimated LD50 was greater than 5000 mg/kg. For the 28 days treatment, an obvious increase in weight was seen as from week 2 at which the group that received the highest dose (1,000 mg/kg) showed significant (p ≤ 0.05) increase in weight compared to all other groups, but subsequently in weeks 3 and 4, significant (p ≤ 0.05) and dose dependent weight increase was observed at all doses administered (Figure 1).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The oral median lethal doses (LD50) of N. laevis stem-bark extract were estimated to be greater than 5000 mg/kg suggesting that the extract was relatively safe and non-toxic. 19 This result is consistent with the report of [27][28] who reported that no mortality was recorded up to 5000 mg/kg in the root and ethanol leaf extracts of N. laevis and the estimated LD50 was greater than 5000 mg/kg. For the 28 days treatment, an obvious increase in weight was seen as from week 2 at which the group that received the highest dose (1,000 mg/kg) showed significant (p ≤ 0.05) increase in weight compared to all other groups, but subsequently in weeks 3 and 4, significant (p ≤ 0.05) and dose dependent weight increase was observed at all doses administered (Figure 1).…”
Section: Resultssupporting
confidence: 91%
“…The increase in creatinine and urea in this study agrees with the previous study by. 28 The kidney histology in this study also showed tubular necrosis and glomerular necrosis with lymphocyte hyperplasia that might have caused this increase in creatinine and urea and increase in systemic lymphocyte seen in this study. Sodium (Na + ) and Clions are usually the predominant cation and anion of the extracellular fluid (ECF).…”
Section: Resultssupporting
confidence: 62%